Estudio de factibilidad para la creación de una empresa procesadora y comercializadora de productos naturistas derivados de la estevia, en la ciudad de Cali (2011)
In the contemporary world, as in all times, human beings in search of a physical balance and spirit, has developed a vast range of products and services that allow you to find better health. In this sense, there are derivatives of existing flora, whose use is unknown and also the medicinal benefits of them were ignored. Based on the above assumptions, the authors of this project: creation of a producer and marketer "NATUESTEVIA", entered the investigation of stevia, this being a clump of Guarani origin have traditionally been used as sweeteners in the population of Paraguay. But also to possess medicinal qualities, such as healing, be suitable for diabetics, helping to eliminate triglycerides and weight loss. Accordingly, this project demonstrates the feasibility of creating a company that, in principle only be devoted to the development of stevia powder for use as sweeteners, not often used raw as stevia and cream for acne control and spots on the skin, for purely aesthetic Throughout all phases of analysis, one of which undergo the idea of a filtering process which is shown as the project ends up being viable, moreover, to be innovative to contribute to employment generation and the extent of their consumption in Colombia, given the form as simple as you can get both products.